Recruitment and Activation of RSK2 by HIV-1 Tat - Hetzer, Claudia; Bisgrove, Dwayne; Cohen, Michael S.; Pedal, Angelika; Kaehlcke, Katrin; Speyerer, Anja; Bartscherer, Kerstin; Taunton, Jack; Ott, Melanie (PloS one, 2007)
The transcriptional activity of the integrated HIV provirus is dependent on the chromatin organization of the viral promoter and the transactivator Tat. Tat recruits the cellular pTEFb complex and interacts with several chromatin-modifying enzymes, including the histone acetyltransferases p300 and PCAF. Here, we examined the interaction of Tat with activation-dependent histone kinases, including the p90 ribosomal S6 kinase 2 (RSK2). Dominant-negative RSK2 and treatment with a small-molecule inhibitor of RSK2 kinase activity inhibited the transcriptional activity of Tat, indicating that RSK2 is important for Tat function. Reconstitution of RSK2 in cells from subjects with a genetic defect in RSK2 expression (Coffin-Lowry syndrome) enhanced Tat transactivation. Tat interacted with RSK2 and activated RSK2 kinase activity in cells. Both properties were lost in a mutant Tat protein (F38A) that is deficient in HIV transactivation. Our data identify a novel reciprocal regulation of Tat and RSK2 function, which might serve to induce early changes in the chromatin organization of the HIV LTR.